2016
DOI: 10.1007/s00586-016-4400-0
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic sagittal plane variations between patients with thoracic adolescent idiopathic scoliosis and healthy adolescents

Abstract: In this 2D analysis of moderate AIS, Lenke 1 curves exhibited normal thoracic sagittal parameters, which brings into question the effect of lordosis on the development of single thoracic curves. Lenke 3 curves exhibited lower thoracic segmental hypokyphosis, and the type 2 showed upper segmental hyperkyphosis. These results should be considered when planning a surgical strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Many previous studies demonstrated the regional flattening of the thoracic sagittal profile on lateral radiographs, as a result of the rotated apical lordosis [18][19][20]. Not all thoracic spines in AIS, however, present as a hypokyphosis on lateral radiographs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many previous studies demonstrated the regional flattening of the thoracic sagittal profile on lateral radiographs, as a result of the rotated apical lordosis [18][19][20]. Not all thoracic spines in AIS, however, present as a hypokyphosis on lateral radiographs.…”
Section: Discussionmentioning
confidence: 94%
“…Clément et al noted that approximately half of the primary thoracic curves present as a normokyphosis on lateral radiographs when the regional kyphosis is considered [19]. Also, Pizones et al demonstrated patients with severe AIS were on average more hypokyphotic than healthy adolescents and that double thoracic curves were associated with a high thoracic kyphosis [20]. In many previous studies, however, only severe/preoperative AIS cases were included and the individual variability in concomitant coronal spinal deformation and sagittal alignment was not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, at present it is difficult to distinguish physiological from pathological cervical spine alignments in AIS patients. The known global pathologic effects of scoliosis include a deforming coronal deviation of the spine with a concomitant rotation of vertebrae and a flattening of the sagittal profile [11, 12]. In recent studies of adult patients, it has been shown that sagittal alignment has a strong correlation with health-related quality of life scores [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic alignment is often cited as being hypo-kyphotic or even lordotic in many cases of AIS [ 11 22 23 ]. A study performed by Pizones et al [ 24 ] analyzed sagittal parameters for AIS patients based on their Lenke curve type and found that in patients with moderate AIS, Lenke type 1 curves exhibited normal thoracic sagittal parameters, whereas type 3 had lower thoracic segmental hypo-kyphosis and type 2 had upper segmental hyper-kyphosis. Sangole et al [ 25 ] even used 3D reconstructions of the spine illustrating that type 1 curves can be broadly divided into normo-kyphotic and hypo-kyphotic group.…”
Section: Discussionmentioning
confidence: 99%